2008
DOI: 10.1177/0885412207314011
|View full text |Cite
|
Sign up to set email alerts
|

The Social Impacts of Wetland Mitigation Policies in the United States

Abstract: Concern over the threat to wetlands from urban development has increased with rising levels of suburbanization.This article provides an extensive overview of the literature on the history and structure of U.S. wetland conservation policy. The authors focus on regulations that permit wetland destruction in return for mitigation of wetland damage and highlight concerns that current wetland mitigation policies may lead to the redistribution of wetland benefits among specific population groups. Researchers and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…To help inform impact mitigation, the scientific community has responded with decades of research establishing best practices for applying the mitigation hierarchy to biodiversity impacts (Race and Fonseca, 1996;Geneletti, 2002;Landis, 2003;BenDor et al, 2008;Canter and Ross, 2010;BBOP, 2012b). Despite these efforts, the approach has fallen short in practice for both biodiversity and the benefits it provides to society-ecosystem goods and services (collectively referred to as ecosystem services, or ES, for simplicity).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To help inform impact mitigation, the scientific community has responded with decades of research establishing best practices for applying the mitigation hierarchy to biodiversity impacts (Race and Fonseca, 1996;Geneletti, 2002;Landis, 2003;BenDor et al, 2008;Canter and Ross, 2010;BBOP, 2012b). Despite these efforts, the approach has fallen short in practice for both biodiversity and the benefits it provides to society-ecosystem goods and services (collectively referred to as ecosystem services, or ES, for simplicity).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the U.S., wetlands damaged by development in urban centers are being mitigated for in more rural areas with lower population densities. Even if these mitigation actions meet biodiversity mitigation needs, they will still fail to return wetland-related ecosystem service benefits to the people who have lost them (BenDor et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The typical objective of this type of research is to characterize gains and losses of wetland functions resulting from the process of mitigation. Others yet discuss the human-related values of preserving natural wetlands (Bendor 2008;Burgin 2010;Johnson and Pflugh 2008;Kaplowitz and Kerr 2003;Lupi and others 2002).…”
Section: Michigan's Wetland Regulationsmentioning
confidence: 96%
“…This arguably creates a large subsidy for industry and land developers who are able to buy credits in a wetland bank for far less money than they receive when their product is sold in the marketplace. While private interests gain considerably in this arrangement, the public largely pays this subsidy in the form of lost ecosystem goods and services (de Groot et al 2010;Mitsch and Gosselink 2000), and there are often unanticipated social costs associated with the redistribution of wetlands through the use of compensation (BenDor et al 2008;BenDor et al 2007). …”
Section: Wetlands Are Economically Undervaluedmentioning
confidence: 99%
“…Despite the continued reliance on this sequence in wetland decision making, there is broad agreement among scholars, scientists, policymakers, regulators, and the regulated community that the first and most important step in the mitigation sequence, avoidance, is ignored more often than it is implemented (Burgin 2010;ELI 2009;Hough and Robertson 2009;Murphy et al 2009a). While many studies have shown that compensatory laws and policies have not been effective in maintaining wetland area and function (for example, Spieles 2005;Cole and Shafer 2002;NRC 2001;Malakoff 1998;Roberts 1993;Zedler 1996), and often have unintended social impacts (see BenDor et al 2008;BenDor et al 2007;Ruhl and Salzman 2006), few explicate why these laws and policies have failed, or suggest alternative approaches to regulating and managing wetland impacts.…”
mentioning
confidence: 99%